2018
DOI: 10.1299/mej.17-00398
|View full text |Cite
|
Sign up to set email alerts
|

Effects of friction welding conditions on tensile strength of friction welded joint between 5052 Al alloy and pure copper

Abstract: This paper described the tensile strength of friction welded joint between Al-Mg alloy (JIS A5052) and pure copper (OFC). In particular, the joining phenomena during the friction process and the effects of friction welding condition such as friction pressure, friction time and forge pressure on the joint strength have been investigated, and the metallurgical characteristics of joints have been also observed and analyzed. The adjacent region of the weld interface at the A5052 side was upset during the friction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…An enormous amount of IMCs appeared in the half-radius zone and the periphery zone, but much fewer IMCs appeared in the central zone [90]. To control the thickness of IMCs, in addition to optimizing the welding process [91], it can be achieved by adding a suitable interlayer to the substrate [92]. and the periphery zone, but much fewer IMCs appeared in the central zone [90].…”
Section: Friction Weldingmentioning
confidence: 99%
See 1 more Smart Citation
“…An enormous amount of IMCs appeared in the half-radius zone and the periphery zone, but much fewer IMCs appeared in the central zone [90]. To control the thickness of IMCs, in addition to optimizing the welding process [91], it can be achieved by adding a suitable interlayer to the substrate [92]. and the periphery zone, but much fewer IMCs appeared in the central zone [90].…”
Section: Friction Weldingmentioning
confidence: 99%
“…and the periphery zone, but much fewer IMCs appeared in the central zone [90]. To co trol the thickness of IMCs, in addition to optimizing the welding process [91], it can achieved by adding a suitable interlayer to the substrate [92]. The grain and second-phase particle evolution of aluminum alloys during frictio welding is also heterogeneous and affects the final properties of the joint.…”
Section: Friction Weldingmentioning
confidence: 99%
“…Many process parameters, including rotation speed, friction time, friction pressure, forging time, and forging pressure, will affect the flashes and interface morphology, which determines the mechanical properties of the joint. Kimura et al [23,24] studied the effect of friction pressure, friction time, and forging pressure on the UTS of A5052 Al/pure Cu joints using the CDFW. They found that higher strength-efficient joints can be obtained when using a lower friction pressure, a higher forging pressure, and a proper friction time.…”
Section: Introductionmentioning
confidence: 99%